Ecological, morphological, and molecular diversification in a clade of Melanesian Ethmostigmus centipedes (Chilopoda: Scolopendromorpha), with the description of 2 new species - Weijola, Valter; Edgecombe, Greg; Iova, Bulisa; Martínez-Muñoz, Carlos; Sjöqvist, Conny; Vahtera, Varpu (Oxford University Press, 2026)
Populations of the large scolopendrid centipede Ethmostigmus Pocock 1898, from five islands of the Bismarck volcanic arc between New Guinea and New Britain comprise a monophyletic group within which three species can be identified based on each forming a strongly supported clade based on concatenated sequence data for three genes, diagnostic morphological characters, and ecology. Two species occurred in sympatry on four of the islands, and all three species are sympatric on the island of Umboi. The two best-sampled and most widely geographically overlapping species are each other’s closest relative, one of them only collected from the ground and the other from trees, a pattern consistent across all islands on which they occur. The tree-dwelling species, Ethmostigmus arboreus sp. nov., is distinguished from the ground species, Ethmostigmus platycephalus (Newport, 1845), by having longer legs. This pair’s sister species, Ethmostigmus krausi sp. nov. from the islands of Umboi and Sakar, is readily distinguished by rugose and coarsely granulate tergal sculpture. This radiation exhibits ecological partitioning at a spatial scale that has not previously been documented in centipedes.